Pengaruh Jumlah Produksi Kakao, Harga Kakao Dunia, Nilai Tukar, dan Harga Ekspor Kakao terhadap Ekspor Kakao di Indonesia - Adrine Gladia Meidrieswida (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2018)
This study aims to analyze the development of cocoa commodity exports in Indonesia. This study uses time series data from 2002 to 2016 and processed using SPSS. The independent variables in this study are the Total Cocoa Production, World Cocoa Prices, Exchange Rates, and Cocoa Export Prices with the dependent variable namely Indonesian Cocoa Exports. Simultaneous test results show that Cocoa Production Amount, World Cocoa Prices, Exchange Rates, and Cocoa Export Prices simultaneously have a significant effect on Cocoa Exports in Indonesia. While the partial test results indicate that the variable Cocoa Production Amount, World Cocoa Prices, Exchange Rates, and Cocoa Export Prices are partially not significantly influence the Cocoa Export in Indonesia